2006
DOI: 10.1038/nsmb1058
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid formation under physiological conditions proceeds via a native-like folding intermediate

Abstract: Although most proteins can assemble into amyloid-like fibrils in vitro under extreme conditions, how proteins form amyloid fibrils in vivo remains unresolved. Identifying rare aggregation-prone species under physiologically relevant conditions and defining their structural properties is therefore an important challenge. By solving the folding mechanism of the naturally amyloidogenic protein beta-2-microglobulin at pH 7.0 and 37 degrees C and correlating the concentrations of different species with the rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
464
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(496 citation statements)
references
References 48 publications
28
464
4
Order By: Relevance
“…These results parallel the observation that protein aggregation and amyloid fiber formation may arise from accumulation of partially folded intermediates [12] …”
Section: Accepted M Manuscriptsupporting
confidence: 86%
See 1 more Smart Citation
“…These results parallel the observation that protein aggregation and amyloid fiber formation may arise from accumulation of partially folded intermediates [12] …”
Section: Accepted M Manuscriptsupporting
confidence: 86%
“…These are particularly difficult tasks considering the fact that folding intermediates are often only transiently populated and play different mechanistic roles, being either on-pathway productive species, or offpathway kinetic traps that have to unfold for proper folding to take place. Furthermore, it has been suggested that accumulation of folding intermediates may be a crucial step prior to protein aggregation and amyloid fiber formation [12], posing the characterization of these partially structured species as a central problem in structural biology.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In particular, highly abundant proteins with relatively low solubilities are prone to aggregate [88]. An increasing number of neurodegenerative and other varieties of prion and amyloid diseases are now known to be caused by misfolded structures (different 'native' structures) or by aggregation/oligomerization of intermediate conformational states, with propensity for misfolding increased by certain mutations [87,89] (figure 3). Cataracts in the human eye are also found to be caused by accumulation of misfolded proteins [90] and associated with mutations that led to abnormal folding behaviour [91,92].…”
Section: Biophysical Consequences Of Protein Mutations 21 Mutationamentioning
confidence: 99%
“…The occurrence of just a few intermolecular contacts, in a quasi-native folding intermediate, would be sufficient to drive the assembly of amyloids (25)(26)(27)(28). In the light of the previous work on DNA-induced transformation of RepA (20,22,23), there is an inverse correlation between the magnitude of the structural change elicited by each dsDNA sequence (iteron Ն nonspecific Ͼ operator) and the internal order of the resulting WH1-A31V assemblies (irregular Ͻ spheroids Ͻ fibrils).…”
Section: Discussionmentioning
confidence: 99%